MANAJEMEN KURIKULUM FISIKA PEMBELAJARAN BERBASIS PROYEK UNTUK MENDUKUNG KREATIVITAS SISWA - Fauzan, Rizki; Luthfy, Perdana Afif (EduFisika: Jurnal Pendidikan Fisika, 2025)
The decline in creativity indicators, as evidenced in education reports, indicates the necessity of improved instructional management of project-based learning (PjBL) to foster student creativity. This study used an explanatory sequential mixed-methods design. Quantitative data were collected from 108 students (total sampling) using a creativity questionnaire, followed by a qualitative case study through classroom observations and documentation and through interviews involving 12 informants. Quantitative findings reveal that student creativity falls into the moderate category (mean: 87.90), with Originality (19.04%) being the lowest indicator, whereas Flexibility (20.56%) was the highest. Qualitative evidence illustrates the contribution of instructional management practices to creativity indicators through four distinct stages. Planning is executed in a structured, goal-based manner, while Organizing establishes collaborative learning environments. Subsequently, Implementation drives project implementation that encourages discovery and reflection, and continuous Monitoring through authentic assessment that can strengthen student engagement to develop flexibility, elaboration, and problem-solving competencies. However, the originality component requires further improvement through enhanced teacher facilitation. Recommendations emphasize improving teacher competency in project design and authentic assessment to support the development of sustainable student creativity.